Updated concepts in treatment of giant cell tumor of bone. Issue 4 (July 2022) - van der Heijden, Lizz; Lipplaa, Astrid; van Langevelde, Kirsten; Bovée, Judith V.M.G.; van de Sande, Michiel A.J.; Gelderblom, Hans
Abstract : Purpose of review: Giant cell tumors of bone (GCTB) are intermediate, locally aggressive primary bone tumors. For conventional GCTB, surgery remains treatment of choice. For advanced GCTB, a more important role came into play for systemic therapy including denosumab and bisphosphonates over the last decade. Recent findings: In diagnostics, focus has been on H3F3A (G34) driver mutations present in GCTB. The most frequent mutation (G34W) can be detected using immunohistochemistry and is highly specific in differentiating GCTB from other giant cell containing tumors. PD-L1 expression can be used as biological marker to predict higher recurrence risks in GCTB patients. The use of bisphosphonate-loaded bone cement is under investigation in a randomized controlled trial. A new technique consisting of percutaneous microwave ablation and bisphosphonate-loaded polymethylmethacrylate cementoplasty was proposed for unresectable (pelvic) GCTB. Increased experience with use of denosumab raised concern on elevated recurrence rates. However, conclusions of meta-analyses should be interpreted with risk of indication bias in mind. Several small studies are published with short-course denosumab (varying from 3 to 6 doses). One small trial directly compared denosumab and zoledronic acid, with no statistical differences in radiological and clinical outcome, and nonsignificantly higher recurrence rate after denosumab. As bisphosphonates directly target neoplastic stromal cells in GCTB, larger directly comparative trials are still warranted. Summary: Neoadjuvant denosumab is highly effective for advanced GCTB, and a short-course is advised to facilitate surgery, whereas increased recurrence rates remain of concern. Randomized controlled trials are conducted on bisphosphonate-loaded bone cement and on optimal dose and duration of neoadjuvant denosumab. PD-L1 could be a potential new therapy target in GCTB.